1997
DOI: 10.1039/a701781b
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric fate of several alkyl nitrates Part 2UV absorption cross-sections and photodissociation quantum yields

Abstract: The UV absorption cross-sections of methyl, ethyl and isopropyl nitrate between 233 and 340 nm have been measured using a diode array spectrometer in the temperature range 240È360 K. The absorption cross-sections of these alkyl nitrates decrease with increasing wavelength and decrease with decreasing temperature for j [ 280 nm. The photodissociation quantum yield for to produce and was found to be essentially unity at 248 nm using transient UV absorption methods. CHand H atoms in the photodissociation of methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
112
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 24 publications
14
112
1
Order By: Relevance
“…While for alkyl mononitrates 6 C5 the dominant loss process is photolysis (8) (Clemitshaw et al, 1997), alkyl nitrates with more than five C-atoms and multifunctional alkyl nitrates are mainly degraded by OH radicals (9) (Talukdar et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…While for alkyl mononitrates 6 C5 the dominant loss process is photolysis (8) (Clemitshaw et al, 1997), alkyl nitrates with more than five C-atoms and multifunctional alkyl nitrates are mainly degraded by OH radicals (9) (Talukdar et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It is also shown that there is minimal overlap with HONO and no overlap in the spectrum at all with PAN. It has been shown (Carbajo and Orr-Ewing, 2010;Talukdar et al, 1997) that there is no overlap with methyl, ethyl, or isopropyl nitrate -methyl nitrate being a minor impurity in PAN synthesis. There is only very minor overlap in the PLC optics spectrum with PAN, methyl ethyl, and isopropyl nitrate.…”
Section: Possible Photolytic Interferences Of Blcsmentioning
confidence: 99%
“…The data were obtained using the 13-cm pathlength gas cell described in section 2, at a temperature of 294 K. Spectra were recorded typically for 4 different pressures of each alkyl nitrate from 1.5 -17 Torr, with at least three scans per pressure, and the absorption cross sections plotted are the averages of values nitrate from the current work (black) and reference [15] (red); (b) methyl nitrate (black) and n-propyl nitrate (red); (c) isopropyl nitrate (black) and dinitrate A (red), with the latter spectrum from reference [7]. All spectra from the current study were recorded at a temperature of 294 K.…”
Section: Absorption Cross Sectionsmentioning
confidence: 99%
“…[13][14][15] Photochemical destruction of RONO2, RONO2 + h  RO + NO2 (1) releases NOx into the atmosphere and thus contributes to further propagation of the HOx and NOx cycles. RONO2 photolysis to liberate NO2 is generally assumed to occur with quantum yield (Φ 2 ) values of unity, 2-3, 13, 16-18 but to date there has been only limited experimental verification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation